gente preciso de ajuda com função: (deixem as contas por favor)
Anexos:
Soluções para a tarefa
Respondido por
1
y=x²-4x-5
f(-2)=(2)²-4(-2)-5=4+8-5=7 (-2,7)
f(-1)=(-1)²-4(-1)-5=1+4-5=0 (-1,0)
f(0)=-5 (0,-5)
f(1)=1²-4.1-5=1-4-5=-8 (1,-8)
f(2)=2²-4.2-5=4-8-5=-9 (2,-9)
f(3)=3²-4.3-5=9-12-5=-8 (3,-8)
f(4)=4²-4.4-5=16-16-5=-5 (4,-5)
f(5)=5²-4.5-5=25-20-5=0 (5,0)
f(6)=6²-4.6-5=36-24-5=7 (6,7)
y=-x²+4x-3
f(-1)=-(-1)²+4(-1)-3=-1-4-3=-8 (-1,-8)
f(0)=-3 (0,-3)
f(1)=-1²+4.1-3=-1+4-3=0 (1,0)
f(2)=-2²+4.2-3=-4+8-3=1 (2,1)
f(3)=-3²+4.3-3=-9+12-3=0 (3,0)
f(4)=-4²+4.4-3=-16+12-3=-7 (4,-7)
f(5)=-5²+4.5-3=-25+20-3=-8 (5,-8)
f(6)=-6²+4.6-3=-36+24-3=-15 (6,-15)
f(-2)=(2)²-4(-2)-5=4+8-5=7 (-2,7)
f(-1)=(-1)²-4(-1)-5=1+4-5=0 (-1,0)
f(0)=-5 (0,-5)
f(1)=1²-4.1-5=1-4-5=-8 (1,-8)
f(2)=2²-4.2-5=4-8-5=-9 (2,-9)
f(3)=3²-4.3-5=9-12-5=-8 (3,-8)
f(4)=4²-4.4-5=16-16-5=-5 (4,-5)
f(5)=5²-4.5-5=25-20-5=0 (5,0)
f(6)=6²-4.6-5=36-24-5=7 (6,7)
y=-x²+4x-3
f(-1)=-(-1)²+4(-1)-3=-1-4-3=-8 (-1,-8)
f(0)=-3 (0,-3)
f(1)=-1²+4.1-3=-1+4-3=0 (1,0)
f(2)=-2²+4.2-3=-4+8-3=1 (2,1)
f(3)=-3²+4.3-3=-9+12-3=0 (3,0)
f(4)=-4²+4.4-3=-16+12-3=-7 (4,-7)
f(5)=-5²+4.5-3=-25+20-3=-8 (5,-8)
f(6)=-6²+4.6-3=-36+24-3=-15 (6,-15)
Usuário anônimo:
Valeu!
Perguntas interessantes
Matemática,
10 meses atrás
Sociologia,
10 meses atrás
Química,
1 ano atrás
Química,
1 ano atrás
Física,
1 ano atrás